Comparison of D-[F-18]FMAU and L-[F-18]FMAU as PET Imaging Agents for HSV1-TK Gene Expression - Moon, Byung Seok; Jo, Nam Hyun; Lee, Kyo Chul; Ei-Gamal, Mohammed I.; An, Gwang Il; Hong, Su Hee; Choi, Tae Hyun; Choi, Won-Kyoung; Park, Jin-Hun; Cho, Jung-Hyuck; Cheon, Gi Jeong; Oh, Chang-Hyun (KOREAN CHEMICAL SOC, 2010)
D-[(18) F]FMAU and L-[F-18]FMAU are F-18 labeled nucleoside analogue which have been efficiently synthesized in order to be a PET imaging probe D-[F-18]FMAU and L-[F-18]FMAU were compared as PET imaging agents using HSV1-TK gene expressing tumor-bearing mice Their cellular uptake profiles were also compared using MCA and MCA-TK cell lines D-[F-18]FMAU demonstrated higher cellular uptake and higher accumulation in MCA-TK tumor regions than L-[F-18]FMAU On the other hand, L-[F-18]FMAU showed higher MCA-TK/MCA ratio of %ID/g than that of D-[F-18]FMAU L-[F-18]FMAU can be utilized as a good candidate for HSV1-TK PET imaging It can be used for antiviral drug evaluation
Keywords: VIRUS THYMIDINE KINASE; IN-VIVO; DNA-SYNTHESIS; FIALURIDINE; CARCINOMA; THERAPY; FIAU